Prospective sarcopenia outcomes associated with physical performance in individuals aged 55 years and over in Malaysia - Megasari, Intan Meinar; Mat, Sumaiyah; Singh, Devinder Kaur Ajit; Tan, Maw Pin (Frontiers in Public Health, 2023)
Background While the potential of physical performance tests as screening tools for sarcopenia is evident, limited information on relevant reference values for sarcopenia detection. In this study, we aimed to establish the prospective relationship between physical performance tests, including time up and go (TUG), functional reach (FR), gait speed (GS), and hand grip strength (HGS) with five-year sarcopenia risk and to determine suitable cut-off values for screening activities. Method This was a prospective study utilizing data from the Malaysian Elders Longitudinal Research (MELoR) study, which involved community-dwelling older adults aged 55 years and above at recruitment. Baseline (2013–2015) and wave 3 (2019) data were analyzed. Sarcopenia risk was determined using the strength, assistance walking, rising from a chair, climbing stairs, and falls (SARC-F) tool, with SARC-F ≥ 4 indicating sarcopenia. Baseline physical performance test scores were dichotomized using ROC-determined cut-offs. Result Data were available from 774 participants with mean age of 68.13 (SD = 7.13) years, 56.7% women. Cut-offs values for reduced GS, TUG, FR, and HGS were: <0.7 m/s (72.9% sensitivity and 53% specificity), >11.5 s (74.2%; 57.2%), <22.5 cm (73%; 54.2%) and HGS male <22 kg (70.0%; 26.7%) and female <17 kg (70.0%; 20.3%) respectively. Except for FR = 1.76 (1.01–3.06), GS = 2.29 (1.29–4.06), and TUG = 1.77 (1.00–3.13) were associated with increased sarcopenia risk after adjustments for baseline demographics and sarcopenia. Conclusion The defined cut-off values may be useful for the early detection of five-year sarcopenia risk in clinical and community settings. Despite HGS being a commonly used test to assess strength capacity in older adults, we advocate alternative strength measures, such as the sit-to-stand test, to be included in the assessment. Future studies should incorporate imaging modalities in the classification of sarcopenia to corroborate current study findings.